The Development and Practical Use of Information Systems in the Pharmaceutical Industry - Yamamoto, M.; Negi, H.; Tamura, M.; Kawai, T.; Yoda, I.; Kawasaki, T.; Hirata, T.; Sugimura, Y.; Okada, S. (Methods of Information in Medicine, 1993)
To provide information on the efficacy, safety, and quality of medicine promptly and accurately, we have developed two databases: a literature database with numerical data, and a Drug Information database. By an easy-to-use, company-wide information network system, over 1,000 medical representatives in more than 80 offices throughout Japan can retrieve information. Information derived from the system is displayed on the terminal and the original documents are automatically output through a facsimile.
Keywords: Drug Information; Literature Information; Optical Storage; Medical Information Technology